2018
DOI: 10.1149/08509.0069ecst
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanopore Fabrication for Single Molecule Bio Sensor Using Electron Beam Irradiation

Abstract: About sixty years ago, the biological cell counter with an electrical detection technique through a micrometer size orifice was invented by Dr. Coulter. Recently, the ultrafast portable pore device (MinION) with an electrical detection technique was manufactured by Oxford Nanopore Technology. However, high error rates possibly from the electrical double layer formed in the pore channel is initially reported in several journals. Furthermore, considering the fact that the optical detection technique is being uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We also fabricated the nanoslit array with its opening width ranging from 100 nm to ~ 10 nm using 30 keV Ga FIB. The plasmonic effect from the nanoslit array is well known [29][30][31]. Nanoslit fabrication with an opening less than 50 nm is much easier than the circular-type aperture with a diameter of 50 nm or less.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also fabricated the nanoslit array with its opening width ranging from 100 nm to ~ 10 nm using 30 keV Ga FIB. The plasmonic effect from the nanoslit array is well known [29][30][31]. Nanoslit fabrication with an opening less than 50 nm is much easier than the circular-type aperture with a diameter of 50 nm or less.…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of plasmonic nanopore on a pyramid and nanoscale double slits is previously investigated [5][6][7][29][30][31]. It is reported that the light transmission through a conical type aperture is dependent on the polarization and aperture size for ka << 1, where k is the wave vector while a is the radius of the circular aperture [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of plasmonic nano-pore on pyramid and double nanoscale double slits is previously examined [5,6,[20][21][22]. Light transmission through the conical type aperture dependent upon the polarization and aperture size for ka << 1 is well documented, where k is the wave vector and a is the radius of the circular aperture [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…We have also fabricated the optical nanopore with its diameter ranging from 10 nm to 3 nm on the on the flat Au thin membrane by using various surface modifications. [15][16][17][18][19][20] Au-aperture with its diameter ranging from 50 nm to 100 nm was initially drilled by 30 keV Ga focused ion beam technique (FIB), then by using various electron beam irradiations such as field emission electron beam microscopy (FESEM) and transmission electron beam microscopy (TEM), a nanopore with its diameter of 5 nm was formed on the diffused membrane inside the FIB-drilled Au aperture. Optical intensity measurements did not reveal any differences between through the nano-aperture without a diffused Au-C membrane, and through the nano-aperture with a diffused membrane.…”
mentioning
confidence: 99%